Policy Implementation and Performance of HIV Prevention Projects - Ndungu, Anthony; Kidombo, Harriet (Kenya Policy Briefs, 2020)
Despite advancements in adolescent and youth sexual and reproductive health (SRH) programmes, the latest data indicate a persistent high need for services. For example, more than 25% of young women are married by 18, increasing their likelihood of having children at an early age. Nearly 33% of young married women have an unmet need for family planning, meaning they wish to delay childbearing but are not using any method of contraception and are at risk of having an unintended pregnancy. Good health and other physical, moral, and intellectual development outcomes are often mutually reinforcing. For example, healthy children do better in school. Similarly, having more years of schooling provides essential information and skills that are linked to more protective and less risky behaviours. There is also strong evidence that peers and parents are influential in shaping gender norms and attitudes. There is some evidence that schools and teachers also shape norms and attitudes. Evidence of the influence of the media is beginning to emerge. This study focused on understanding and proposing solutions to improved implementation of health promotion projects targeting adolescents in Kenya.
Keywords: HIV